2010
DOI: 10.1515/jpem.2010.130
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume in Obese Adolescents with Nonalcoholic Fatty Liver Disease

Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is the accumulation of excess fat in the liver in the absence of alcohol consumption, which commonly coexists with obesity. NAFLD is associated with increased risk of atherosclerosis and insulin resistance. Mean platelet volume (MPV) is a marker of platelet activation, which is a determinant of atherosclerosis. Aims: The first aim of the present study was to investigate the MPV levels in obese adolescents and compare the MPV levels in patients with and witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 35 publications
5
26
0
6
Order By: Relevance
“…obese adolescents had higher MPV but a lower platelet count. 19 Atorvastatin administration significantly decreased MPV in obese atorvastatin treated rats of our study. Effect of statins in reducing atherothrombotic events has been published widely in bio medical literature, and statins are known to decrease platelet reactivity; however, this effect on newly proposed platelet reactivity marker (i.e.…”
Section: Discussionsupporting
confidence: 50%
“…obese adolescents had higher MPV but a lower platelet count. 19 Atorvastatin administration significantly decreased MPV in obese atorvastatin treated rats of our study. Effect of statins in reducing atherothrombotic events has been published widely in bio medical literature, and statins are known to decrease platelet reactivity; however, this effect on newly proposed platelet reactivity marker (i.e.…”
Section: Discussionsupporting
confidence: 50%
“…Arslan and Makay have demonstrated that MPV levels were higher in obese adolescents with non-alcoholic fatty liver when compared with healthy controls, and other obese patient groups [17]. However, Kilciler et al reported that any significant difference was not found between the patients with non-alcoholic fatty liver disease as for MPV levels [18].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 128 obese adolescents, MPV was significantly higher in obese patients with NAFLD compared with obese patients without NAFLD or controls. This indicates that children with NAFLD have higher CV risk; however, correlation with liver histology was not examined as the diagnosis of NAFLD was made based on ultrasound findings and the presence of elevated liver enzymes [76]. …”
Section: Nafld and Systemic Inflammationmentioning
confidence: 99%